Alphapartitiviruses of Heterobasidion Wood Decay Fungi Affect Each Other's Transmission and Host Growth - Kashif, Muhammad; Jurvansuu, Jaana; Vainio, Eeva J.; Hantula, Jarkko (Frontiers in Cellular and Infection Microbiology, 2019)
Heterobasidion spp. root rot fungi are highly destructive forest pathogens of the northern boreal forests, and are known to host a diverse community of partitiviruses. The transmission of these mycoviruses occurs horizontally among host strains via mycelial anastomoses. We revealed using dual cultures that virus transmission rates are affected by pre-existing virus infections among two strains of H. annosum. The transmission efficacy of mycovirus HetPV15-pa1 to a pre-infected host was elevated from zero to 50% by the presence of HetPV13-an1, and a double infection of these viruses in the donor resulted in an overall transmission rate of 90% to a partitivirus-free recipient. On contrary, pre-existing virus infections of two closely related strains of HetPV11 hindered each other's transmission, but had unexpectedly dissimilar effects on the transmission of more distantly related viruses. The co-infection of HetPV13-an1 and HetPV15-pa1 significantly reduced host growth, whereas double infections including HetPV11 strains had variable effects. Moreover, the results showed that RdRp transcripts are generally more abundant than capsid protein (CP) transcripts and the four different virus strains express unique transcripts ratios of RdRp and CP. Taken together, the results show that the interplay between co-infecting viruses and their host is extremely complex and highly unpredictable.